Accurate Assessment of Blood Loss during Cesarean Delivery Improves Estimation of Postoperative Hemoglobin - Rubenstein, Andrew F.; Block, Michael; Zamudio, Stacy; Douglas, Claudia; Sledge, Sharon; Tully, Griffeth; Thurer, Robert L. (American Journal of Perinatology, 2019)
Objective To determine if accurate blood loss determination during cesarean delivery can improve the prediction of postoperative hemoglobin levels.Study Design This is a retrospective cohort study using visually estimated blood loss (traditional, n = 2,025) versus estimates using a mobile application that photographs sponges and canisters and calculates their hemoglobin content (device, n = 756).Results The correlation between the actual and predicted postoperative day 1 hemoglobin value (PPO1 Hgb) was better in the device group (R2 = 0.519, correlation = 0.720) than in the traditional group (R2 = 0.429, correlation = 0.655) (p = 0.005). For patients in the device group where the estimated blood loss was >1,000 mL (n = 53), the PPO1 Hgb was also better correlated with the actual value (R2 = 0.319, correlation = 0.565) than the predictions using visually estimated blood loss for those patients in the device group whose visual estimation was >1,000 mL (n = 32) (R2 = 0.035, correlation = 0.187) (p = 0.027).Conclusion Implementation of a device that accurately measures blood loss allows for a better prediction of postoperative day 1 hemoglobin concentration than is possible using visual blood loss estimation. This improvement was seen in the entire patient group and was particularly prominent in patients with blood losses of > 1,000 mL.
Keywords: cesarean delivery; blood loss; transfusion; postpartum hemorrhage; quality; improvement